The impact of India-ASEAN free trade agreement on trade flows: An application of augmented gravity model - Prajakta Arote; Hastimal Sagara; Jadhav Chakradhar; Guruprasad Desai; Jadhav Pravin; Din Bandhu (PLoS ONE, 2026)
This study investigates the impact of the India-ASEAN Free Trade Agreement (FTA) on bilateral trade flows through an augmented gravity model. Employing panel data from 1990 to 2022 with 330 observations, the analysis incorporates key determinants such as GDP and population of India and ASEAN countries, tariff rates, geographic distance, historical ties, and levels of democracy, trade openness, and globalization. To address heteroskedasticity and cross-sectional dependency, we utilize Generalized Least Squares (GLS) estimations. Our analysis examines both export and import volumes between India and ASEAN nations. Results from Ordinary Least Squares (OLS) and GLS estimations indicate that ASEAN countries’ GDP positively influences trade volumes, while India’s GDP demonstrates mixed effects. Larger populations in both India and ASEAN countries significantly contribute to trade. Tariff rates and geographic distance are found to have a negative effect on both exports and imports. Interestingly, shared colonial history and language positively impact trade, whereas a common border yields mixed effects across the models. Control variables reveal that trade openness, democracy levels, and globalization have a positive and significant effect on India-ASEAN trade flows. The FTA dummy is positive and highly significant, confirming that AIFTA has substantially increased India’s bilateral trade with ASEAN. Based on these findings, we suggest that enhancing economic growth, mitigating geographic barriers, leveraging historical ties, and promoting trade openness and regional integration are essential strategies to bolster trade between India and ASEAN countries.